Numerical Investigation on Effect of Rounded Cutting-Edge Radius and Machining Parameters in End Milling of AISI H13 Tool Steel - Bakar, Husni Nazra Abu; Ghani, Jaharah A.; Haron, Che Hassan Che (International Journal of Engineering and Technology, 2018)
Rounded cutting-edge radius is commonly applied to finish and semi-finish cutting, precision machining and micro-machining. The optimum effect is closely related to the work and tool material as well as machining parameters. However, for numerous cutting process, the optimal radius of rounded cutting-edge radius and machining parameters applied in the AISI H13 of end-milling is yet unknown Therefore, in improving tool life and cutting tool performance, a suitable design of cutting edge geometry regarding cutting edge-radius and machining parameters need to be examined and properly selected. In this regard, the paper deals to examine the effect of cutting edge-radius in rounded form and machining parameters of cutting force, cutting temperature and chip formation through the end-milling process of AISI H13 using uncoated cemented carbide cutting tool through finite element simulation of Thirdwave AdvantEdge 7.2 software. The machining parameters applied in the simulation setup were 200 and 240m/min of cutting speed, 0.03 and 0.06mm/tooth of feed-rate and axial depth of cut of 0.1 and 0.2mm while width of cut in radial direction was kept constant at 6.0mm. The cutting geometries includes the cutting-edge radius of 0.03 and 0.05mm and 10Â° of rake angle. The obtained results revealed that cutting forces and cutting temperature is increase as depth of cut in axial direction and cutting-edge radius increases while increasing value of speed and feed-rate of cutting resulted in decreasing cutting forces but increasing cutting temperature. The maximum cutting temperature is 674.91â„ƒ. The value obtained is lesser than the AISI H13 austenitizing temperature, therefore a layer known as white layer is supposedly hard to be created based on the cutting geometry and machining parameters applied. Â